Healthcare information technology (IT) and management systems. Part 3 – international experiences in e-prescription - Wdowiak, Leszek; Bojar, Iwona; Horoch, Andrzej (Polish Journal of Public Health, 2009)
One of the most important element in health care information system is the efficiently functioning e-prescription system. Basing on the international experiences, the paper is presenting the proven methods of communication between the project participants, the scope of transmission and the scope of information required for the correct functioning of e-prescription system.The achievements of the following countries in this field have been presented: Denmark, Spain, USA, Czech Republic, Germany, Great Britain, Bulgaria, Estonia, Gibraltar, Norway and Sweden.The analysis of the applied solutions in individual countries concerning e-prescription indicates many convergent elements in the individual projects, nevertheless it points to significant differences in functioning of health care in individual countries. The applied solutions are adapted to the specific character of the legislation of a given country, however many of the elements of good practice or concepts can be used in other countries. The mechanism of e-prescription allows for efficient buying of the prescribed drugs in a chosen drug stores, the analysis of the possible contraindications for dispensing a drug, efficient functioning of the system of prescriptions monitoring, allowing for detecting and eliminating of prescription forgery. This makes improvement of rationalization in financing of health care in a given country, possible.